Determinants of personal accounting applications adoption: A perspective of the centennial generation - Saputri, Selvi; Kholid, Muamar Nur (Jurnal Akuntansi dan Auditing Indonesia, 2026)
This study aims to identify the factors influencing the intention to use a personal accounting application by employing the Technology Acceptance Model (TAM) and the Diffusion of Innovation (DOI) theory. The sampling methods were purposive and convenient, focusing on individuals from the Centennial Generation. A total of 201 respondents were selected based on these criteria. The research employed a quantitative approach. The findings reveal that complexity, relative advantage, and observability enhance perceived usefulness; however, they do not have a positive influence on perceived ease of use. On the other hand, compatibility and trialability have a positive impact on both perceived ease of use and perceived usefulness. Additionally, perceived ease of use has a positive influence on perceived usefulness, and both perceived usefulness and perceived ease of use contribute positively to the intention to use.